2017
DOI: 10.3390/sports5040077
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Association of Movement in Irish Adolescent Youth

Abstract: (1) Background: Research has shown that post-primary Irish youth are insufficiently active and fail to reach a level of proficiency across basic movement skills. The purpose of the current research was to gather cross-sectional baseline data on Irish adolescent youth, specifically the prevalence of movement skills and patterns, in order to generate an overall perspective of movement within the first three years (Junior Certificate level) of post-primary education; (2) Methods: Data were collected on adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 52 publications
5
40
3
1
Order By: Relevance
“…The mastery of object-control skills in this study was demonstrably lower than previously published figures among Irish adolescents [ 17 , 20 ] and Irish children [ 18 , 19 ]. While performance in the locomotor skills of the run and horizontal jump were below previous Irish standards, both the vertical jump and skip were comparable or higher than other Irish childhood and adolescent research [ 17 , 18 , 19 , 20 , 68 ]. In comparison with global studies, performances in the kick, dribble, and balance were lower than previously reported values in British children [ 69 ].…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…The mastery of object-control skills in this study was demonstrably lower than previously published figures among Irish adolescents [ 17 , 20 ] and Irish children [ 18 , 19 ]. While performance in the locomotor skills of the run and horizontal jump were below previous Irish standards, both the vertical jump and skip were comparable or higher than other Irish childhood and adolescent research [ 17 , 18 , 19 , 20 , 68 ]. In comparison with global studies, performances in the kick, dribble, and balance were lower than previously reported values in British children [ 69 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Older individuals often exhibit improved FMS due to increased access to practice, coaching, corrective feedback, and greater physical stature; however, FMS improvements are not always age-determined [ 6 , 72 ]. This study’s findings are supported by previous Irish research that found an age-related decline in object-control proficiency across the second-level school years [ 20 ]. More recent Irish findings indicate a ‘plateau’ of skills from the age of 10, with no further growth in FMS for children aged 11 and 12 [ 19 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations